Pengembangan Media Pembelajaran Fisika Berbasis Mobile Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Aisyiyah Hidayah Ngurahrai; Siska Desy Fatmaryanti; Nurhidayati Nurhidayati (Universitas Muhammadiyah Purworejo, 2019)
Research on the development of mobile-based learning media has been conducted to determine its feasibility, the affect on the improvement of students' critical thinking skill, and effectiveness of the media used in leraning. The type of this research is the development that refers to the ADDIE development model, namely: Analysis, Design, Development, Implementation, and Evaluation. This research was conducted in SMA Negeri 5 Purworejo with the subjects of the trial amounting to 29 students. The instruments used in this study are: validation sheets, learners' responses, learning outcome tests, and learning implementation sheets. Based on the research data obtained from the validation of mobile-based media for learning from four validators namely: three expert lecturers and physics teachers had an overall score 3.56, included in the good category and feasible to use in learning. The improvement of critical thinking skills in the implementation phase obtained N-gain 0.61 and included the medium increase category. The effectiveness of the media used in the assessment learning with learners’ responses received an overall contribution of 84% and included good categories, and was shown by the learning implementation sheet with an overall contribution of 95.8% and included in the excellent category. Thus the development of mobile-based learning media in this study is categorized as good and suitable to use as learning media, and also could help to improve students' critical thinking skills.